A comprehensive model to prioritise lean tools for manufacturing industries: a fuzzy FMEA, AHP and QFD-based approach. (28th September 2020) - Kumar, M. Bhuvanesh; Parameshwaran, R.
This paper describes a start-to-end lean tools (LTs) selection model for manufacturing industries. The integrated model utilises value stream mapping (VSM) and plant layout for identifying wastes from current state of the organisation. For prioritising the wastes along with associated risks, failure mode and effects analysis (FMEA) is adopted. Selection of LTs is done using analytic hierarchy process (AHP) and house of quality (HoQ). This model utilises fuzzy logic (FL) to convert the linguistic judgements into numerical values for computation. Future state map deployed with the shortlisted LTs is developed to compare current and future states. The model is applied in PVC pipe manufacturing industry and the results show notable improvements. The raw material saving of 2.5 kg, 3% reduction of value added time, 7% reduction of non-value added time and 5% reduction of lead time in the production of PVC pipes per batch are obtained in future state.